Patients' motives for choosing a physician: comparison between conventional and complementary medicine in Swiss primary care - Busato André; Wapf Victoria (BMC, 2007)
Abstract Background The study is part of a nationwide evaluation of complementary and alternative medicine (CAM) in primary care in Switzerland. The Objective was to identify patients' expectations and reasons governing the choice of complementary medicine compared with conventional primary care (CONV). Methods The data were derived from the PEK study (Programm Evaluation Komplementärmedizin), which was conducted in 2002-2003 with 7879 adult patients and parents of 1291 underage patients, seeking either complementary (CAM) or conventional (CONV) primary care. The study was performed as a cross-sectional survey. The respondents were asked to document their (or their children's) self-perceived health status, reasons governing their choice, and treatment expectations. Physicians were practicing conventional medicine and/or complementary methods (homeopathy, anthroposophic medicine, neural therapy, and traditional Chinese medicine). Reasons governing the choice of physician were evaluated on the basis of a three-part classification (physician-related, procedure-related, and pragmatic/other reasons) Results and Discussion Patients seeing CAM physicians tend to be younger and more often female. CAM patients referred to procedure-related reasons more frequently, whereas pragmatic reasons dominated among CONV patients. CAM respondents expected fewer adverse side effects compared to conventional care patients. Conclusion The majority of alternative medicine users appear to have chosen CAM mainly because they wish to undergo a certain procedure; additional reasons include desire for more comprehensive treatment, and expectation of fewer side-effects.